Study Of Adenosine Deaminase Level In Bronchoalveolar Lavage Fluid And Its Correlation With Genxpert In Sputum Negative Suspected Pulmonary Tuberculosis And Suspected Lung Malignancy. (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction: Tuberculosis (TB) has been one of the health problems in the world.  Diagnosis of pulmonary tuberculosis based on finding of AFB in the  sputum has several limitations and mycobacterial culture is time  consuming. So we decided to evaluate biomarker like Adenosine  Deaminase (ADA) activity in Bronchoalvolar Lavage(BAL) fluid .Objectives: To study level of BAL ADA in sputum negative suspected  cases of pulmonary tuberculosis and correlate it with BAL GenXpert  (Cartridge Based Nucleic Acid Amplification) result. Method: We have enrolled suspected sputum negative pulmonary TB  and suspected lung malignancy patients (as control). Total 33 patients -  17 suspected sputum negative pulmonary TB, 16 suspected lung  malignancy were enrolled in study and subjected to bronchoscopy and  BAL fluid was submitted for ADA level and GenXpert for TB. Result: Increased BAL ADA level was found in suspected sputum  negative pulmonary TB as compare to suspected malignancy. Increased  BAL level was well correlared with GenXpert positivity in suspected TB  group.  Conclusion: BAL fluid ADA can be useful tool for early diagnosis of  suspected sputum negative pulmonary TB.
Keywords: Adenosine Deaminase; Bronchoalveolar Lavage F Genxpert; Pulmonary Tuberculosis; Suspected Lung Malignancy